Nanostructured 2D MoS2 honeycomb and hierarchical 3D CdMoS4 marigold nanoflowers for hydrogen production under solar light - Kadam, Sunil R.; Late, Dattatray J.; Panmand, Rajendra P.; Kulkarni, Milind V.; Nikam, Latesh K.; Gosavi, Suresh W.; Park, Chan J.; Kale, Bharat B. (Journal of Materials Chemistry A, 2015)
Unique two dimensional (2D) honeycomb layered MoS2 nanostructures and hierarchical 3D marigold nanoflowers of CdMoS4 were designed using a template free and facile solvothermal method. The MoS2 structure is depicted with a sheet like morphology with lateral dimensions of 5-10 mu m and a thickness of similar to 200 nm and a honeycomb nanostructure architecture produced via the self-assembling of vertically grown thin hexagonal nanosheets with a thickness of 2-3 nm. The 3D CdMoS4 marigold nanoflower architecture comprised thin nanopetals with lateral dimensions of 1-2 mu m and a thickness of a few nm. The CdMoS4 and MoS2 structures displayed hydrogen ( H-2) production rates of 25 445 and 12 555 mu mol h(-1) g(-1), respectively. The apparent quantum yields of hydrogen production were observed to be 35.34% and 17.18% for CdMoS4 and MoS2, respectively. The 3D nanostructured marigold flowers of CdMoS4 and honeycomb like 2D nanostructure of MoS2 were responsible for higher photocatalytic activity due to inhibition of the charge carrier recombination. The prima facie observation of H-2 production showed that the ternary semiconductor confers enhanced photocatalytic activity for H-2 generation due to its unique structure. Such structures can be designed and implemented in other transition metal dichalcogenide based ternary materials for enhanced photocatalytic and other applications.

Architecture of 2D MoS2 nanosheets and 3D CdMoS4 marigold flowers: consequence of annealing on field emission performance - Kadam, Sunil R.; Suryawanshi, Sachin R.; Panmand, Rajendra P.; Mate, Vivek R.; More, Mahendra A.; Late, Dattatray J.; Kale, Bharat B. (Microporous and Mesoporous Materials, 2016)
Herein, we report the field electron emission investigations on template free solvothermally synthesized layered MoS2 nanosheets as well as novel phase of CdMoS4 nanoflowers at the base pressure of similar to 1 x 10(-8) mbar. The turn-on field, threshold field and maximum emission current densities for both MoS2 and CdMoS4 are strongly influenced by thermal annealing in inert atmosphere. The turn on field, required to draw emission current density of 1 mu A/cm(2) is found to be 5.8 and 3.2 V/mu m for pristine and annealed MoS2 at 400 degrees C. In case of as prepared and annealed CdMoS4 sample the turn on field values are found to be similar to 6.2 and 5.0 V/mu m, respectively. The emission current versus time (I-t) plot measured at the preset current values of similar to 1 mu A for pristine and annealed sample indicates stable operation of the emitter. The emission current fluctuations for annealed sample are observed to be less as compared with the pristine sample due to conditioning of the emitter, thereby showing highly stable nature of emitter. Thus, the present result demonstrates the potential of annealed MoS2 nanosheets and CdMoS4 nanoflowers as an emerging materials for micro/nanoelectronics and flat panel field emission display applications. (C) 2016 Elsevier Inc. All rights reserved.
Keywords: field emission; MoS2 and CdMoS4; Nanoflowers; nanosheets

In situ fabrication of highly crystalline CdS decorated Bi2S3 nanowires (nano-heterostructure) for visible light photocatalyst application - Panmand, Rajendra P.; Sethi, Yogesh A.; Deokar, Rajashree S.; Late, Dattatray J.; Gholap, Haribhau M.; Baeg, Jin-Ook; Kale, Bharat B. (RSC Advances, 2016)
In situ synthesis of the orthorhombic Bi2S3 nanowires decorated with hexagonal CdS nanoparticles (nano-heterostructure) has been demonstrated by a facile solvothermal method. The tiny 5-7 nm CdS spherical nanoparticles are decorated on the surfaces of 30-40 nm Bi2S3 nanowires, successfully. Structural, morphological and optical studies clearly show the existence of CdS on the nanowires. A possible sequential deposition growth mechanism is proposed on the basis of experimental results to reveal the formation of the nano heterostructure. The heterostructures have been used as a photocatalyst for hydrogen production as well as degradation of methylene blue under solar light. The maximum hydrogen evolution i.e. 4560 and 2340 mu mol h(-1) 0.5 g was obtained from H2S splitting and glycerol degradation for Bi2S3 NWs decorated with CdS nanoparticles (nano-heterostructure) which is higher than that of the Bi2S3 NWs (3000 and 1170 mu mol h(-1) 0.5 g, respectively). The enhanced photocatalytical hydrogen evolution efficiency of the heterostructures is mainly attributed to its nanostructure. In the nano heterostructure, the CdS nanoparticles control the charge carrier transition, recombination, and separation, while the Bi2S3 nanowire serves as a support for the CdS nanoparticles. The photogenerated electron's migration is faster than the holes from the inside of a CdS nanoparticle to its surface or to the phase interface, resulting in a relatively higher hole density inside the CdS nanoparticle leaving electron density at surface of the Bi2S3 NWs. This influences the photocatalytic activity under solar light. Such nano-heterostructures may have potential in other photocatalytic reactions.

Situ fabrication of highly crystalline CdS decorated Bi2S3 nanowires (nano-heterostructure) for visible light photocatalyst application - Panmand, Rajendra P.; Sethi, Yogesh A.; Deokar, Rajashree S.; Late, Dattatray J.; Gholap, Haribhau M.; Baeg, Jin-Ook; Kale, Bharat B. (RSC Advances, 2016)
In situ synthesis of the orthorhombic Bi2S3 nanowires decorated with hexagonal CdS nanoparticles (nano-heterostructure) has been demonstrated by a facile solvothermal method. The tiny 5-7 nm CdS spherical nanoparticles are decorated on the surfaces of 30-40 nm Bi2S3 nanowires, successfully. Structural, morphological and optical studies clearly show the existence of CdS on the nanowires. A possible sequential deposition growth mechanism is proposed on the basis of experimental results to reveal the formation of the nano heterostructure. The heterostructures have been used as a photocatalyst for hydrogen production as well as degradation of methylene blue under solar light. The maximum hydrogen evolution i.e. 4560 and 2340 mu mol h(-1) 0.5 g was obtained from H2S splitting and glycerol degradation for Bi2S3 NWs decorated with CdS nanoparticles (nano-heterostructure) which is higher than that of the Bi2S3 NWs (3000 and 1170 mu mol h(-1) 0.5 g, respectively). The enhanced photocatalytical hydrogen evolution efficiency of the heterostructures is mainly attributed to its nanostructure. In the nano heterostructure, the CdS nanoparticles control the charge carrier transition, recombination, and separation, while the Bi2S3 nanowire serves as a support for the CdS nanoparticles. The photogenerated electron's migration is faster than the holes from the inside of a CdS nanoparticle to its surface or to the phase interface, resulting in a relatively higher hole density inside the CdS nanoparticle leaving electron density at surface of the Bi2S3 NWs. This influences the photocatalytic activity under solar light. Such nano-heterostructures may have potential in other photocatalytic reactions.

Facilitated lithium storage in hierarchical microsphere of Cu2S-MoS2 ultrathin nanosheets - Kadam, Sunil R.; Kalubarme, Ramchandra S.; Deshmukh, Shrutika P.; Panmand, Rajendra P.; Kawade, Ujjwala, V.; Kulkarni, Milind, V.; Deo, Shriniwas S.; Gosavi, Suresh W.; Kale, Bharat B. (ChemistrySelect, 2018)
Considering the high energy density Lithium ion batteries have become one of the best option for next-generation energystorage technologies. Transition metal chalcogenide nanomaterials are promising electrodes for Lithium-ion batteries. Molybdenum based layered chalcogenide materials wisely studied for rechargeable Li-ion batteries, due to its two-dimensional (2D) layered structure and better specific capacity. The three-dimensional (3D) synthesis of microsphere by ultrathin nanosheets is necessary for practical applications. Herein, the fabrication of a unique hierarchical 2D layered Cu2S-MoS2 nanostructure was (ultrathin nanosheets) demonstrated via in situ assembling of two-dimensional (2D) growths in facile solvothermal technique. The structural study reveals the existence of Cubic Cu2S and Rhombohedral MoS2 phase. Morphological study by FESEM and TEM shows unique ultrathin nanosheets of similar to 10 nm thickness self-assembled in the form of layered microsphere. In Li- ion storage testing, Cu2S-MoS2 electrode exhibited good specific discharge capacity of 651 mAhg(-1) at 50 mAg(-1) applied current and maintained 320 mAhg(-1) after 100 cycles. The facilitated advanced electrochemical performance attributed to layered ultrathin Cu2S-MoS2 composite nanosheets.